Threads-based peer feedback in developing EFL students’ writing skills: Perceptions and challenges - Siti Rowiyah; Bambang Yudi Cahyono; Ekaning Dewanti Laksmi (JEELS (Journal of English Education and Linguistics Studies), 2025)
The inherent complexity of writing frequently engenders anxiety in English as a Foreign Language (EFL) students, leading to the necessity of teaching writing innovatively through technology-enhanced approaches. Although extensive previous studies have investigated the implementation of technological tools in teaching writing, a significant research gap exists regarding learners’ perceptions and reception of these tools, especially integrating Threads platform in serving peer feedback. Therefore, the present study aims to investigate EFL students’ perceptions on the effectiveness of Threads-based peer feedback as a mechanism for writing skill development. Employing a mixed method, the investigation collected the data through a questionnaire distributed to 20 EFL students experienced in Threads-based peer feedback in a writing course. Data from the close-ended questionnaire were analyzed using descriptive statistics through SPSS 24 version, while the results of the open-ended questionnaire were analyzed qualitatively through thematic analysis. Findings reveal that the students perceived Threads-based peer feedback effectively facilitated students' impressive learning experience and enhanced engagement as well as comprehension through noticeable technological features. The students also perceived that Threads-based peer feedback improved their writing skills in multiple dimensions. However, certain practical and technical challenges remain throughout Threads-based feedback processes. This research is pedagogically significant to the emerging body of knowledge on the updated digital tool integration in language teaching, especially advanced English writing.